Superconducting and mechanical properties of the bulk Bi(pb)SCCO system prepared via solid state and ammonium nitrate precipitation methods - Safran, S.; Kilicarslan, E.; Ozturk, H.; Alp, M.; Akdogan, M.; Asikuzun, E.; Ozturk, O.; Kilic, A. (Elsevier BV, 2015)
Abstract We have investigated the effect of preparation method on superconducting and mechanical properties of Bi(Pb)-2223 bulk samples using Bi 1.85 Pb 0.35 Sr 2 Ca 2 Cu 3 O 10±y stoichiometry. Solid-state reaction and ammonium nitrate precipitation methods have been used for fabrication of the bulk samples. In addition, the effect of annealing time on BSCCO samples have been studied. Structural, electrical, magnetic and microhardness analyses of samples are performed by the X-ray powder diffraction (XRD), the Scanning Electron Microscopy (SEM), DC resistivity, AC susceptibility and Vickers microhardness test. The critical transition temperature, phase purity, surface morphology and crystallinity of the prepared bulk samples are compared with each other. Elasticity ( E ), brittleness ( B i ), fracture toughness ( K IC ) and yield strength ( Y ) values are also determined according to annealing time, applied load and production parameters of materials.
Keywords: Magnetic Properties; Electrical Properties; Mechanical Properties; Superconductors